THE DIGITAL GAMING ATTITUDE SCALE (DGAS): Reliability and Validity Study - TEKKURŞUN DEMİR , Gönül and MUTLU BOZKURT, Tuğba (Sportif Bakış: Spor ve Eğitim Bilimleri Dergisi, 2019)
In this study, it was aimed to develop a tool that can measure attitudes of university students towards digital gaming in a valid and reliable way. 368 university students studying at Gazi University Faculty of Sports Sciences in the 2018-2019 academic year participated in the study. In this study, a mixed design, integrating qualitative and quantitative research designs, was used. In the qualitative step of the study, students were asked about digital gaming, and item pooling was conducted. In the quantitative step, reliability and validity studies were conducted by using SPSS 23 and Lisrel 8.8 programs. According to Exploratory Factor Analysis (EFA), a structure with three subscales consisting of 18 items was obtained. The scale consists of Cognitive (5 items), Affective (5 items) and Behavioral (8 items) sub-scales. Following exploratory factor analysis, a confirmatory factor analysis (CFA) was performed and an evidence was obtained that fit indices of the scale obtained according to CFA were within the acceptable range. Subsequently, item and reliability analyses were conducted for the scale. In this context, the total variance ratio explained by the scale was 65.11% and Cronbach’s Alpha was .82. As a result, it was found that the Digital Gaming Attitude Scale is a tool that can accurately and reliably measure participants’ attitude towards digital gaming.